(untitled) - Mitra, Jay (London, 2017)
The Business of Innovation sets out to track, trace and provide testimonies of innovation practice in small to large-scale organisations from countries around world. Through a combination of contemporary economic and social theory, and an array of practical examples from a wide range of sectors and industries, Jay Mitra offers critical insight into how global innovation works, where it works and most importantly, who makes it work, with an emphasis on innovative women. Suitable for postgraduate, doctoral and MBA students on business management and innovation courses and practitioners looking for a critical insight into the business of innovation.
Keywords: Creative ability in business,Khả năng sáng tạo trong kinh doanh